Challenges of identification and anonymity in time-continuous data from medical environments - Hammer, Freimut; Strufe, Thorsten (Frontiers in Digital Health, 2025)
In medical environments, time-continuous data, such as electrocardiographic records, necessitates a distinct approach to anonymization due to the paramount importance of preserving its spatio-temporal integrity for optimal utility. A wide array of data types, characterized by their high sensitivity to the patient’s well-being and their substantial interest to researchers, are generated. A significant proportion of this data may be of interest to researchers beyond the original purposes for which it was collected. This necessity underscores the pressing need for effective anonymization methods, a challenge that existing approaches often fail to adequately address. Robust privacy mechanisms are essential to uphold patient rights and ensure informed consent, particularly within the framework of the European Health Data Space. This paper explores the challenges and opportunities inherent in developing a novel approach to anonymize such data and devise suitable metrics to assess the efficacy of anonymization. One promising approach is the adoption of differential privacy to account for temporal context and correlations, making it suitable for time-continuous data.